2015
DOI: 10.1128/iai.00231-15
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Apoptotic Effects of Recombinant Subtilase Cytotoxin Variants of Shiga Toxin-Producing Escherichia coli

Abstract: In this study, the cytotoxicity of the recently described subtilase variant SubAB 2-2 of Shiga toxin-producing Escherichia coli was determined and compared to the plasmid-encoded SubAB 1 and the chromosome-encoded SubAB 2-1 variant. The genes for the respective enzymatic active (A) subunits and binding (B) subunits of the subtilase toxins were amplified and cloned. The recombinant toxin subunits were expressed and purified. Shiga toxin-producing Escherichia coli (STEC) strains are zoonotic bacterial pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Hauser et al. () demonstrated an important cytotoxic effect on Vero cells for SubAB 1 , which is the subtilase variant with the highest cytotoxicity (Funk et al., ) and also the one that predominated in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Hauser et al. () demonstrated an important cytotoxic effect on Vero cells for SubAB 1 , which is the subtilase variant with the highest cytotoxicity (Funk et al., ) and also the one that predominated in this study.…”
Section: Discussionsupporting
confidence: 54%
“…These variants share an overall identity in their amino-acid sequences of 94.5% for the A-subunits and 92.4% for the B-subunits, but they have distinct genetic localizations in the STEC genomes. Since previous studies showed differences in CD 50 values of these variants [24], we were interested to further characterize them in their ability to form active complexes.…”
Section: Purification Of Suba and Subb Subunitsmentioning
confidence: 99%
“…The His-tagged subunits of SubAB1 and SubAB2-2 were expressed in E. coli C41 (DE3) cells as described elsewhere [24]. The purification protocols for these subunits established by Funk et al [24] were improved by adding size-exclusion chromatography steps to allow the removal of imidazole and further impurities of the tagged subunits as described below.…”
Section: Purification Of Suba and Subb Subunitsmentioning
confidence: 99%
See 2 more Smart Citations